POSSIBLE USE OF LENGTH-BASED SPAWNING POTENTIAL RATIO FOR SKIPJACK (Katsuwonus pelamis) IN INDONESIA’S ARCHIPELAGIC WATERS - Fayakun Satria; Lilis Sadiyah (Indonesian Fisheries Research Journal, 2017)
A harvest strategy development for skipjack tuna (Katsuwonus pelamis - SKJ) fishery within Indonesia’s archipelagic waters (Indonesian Fisheries Management Areas - FMAs 713-715) has been initiated, which is mandated within its National Tuna, Skipjack and Neritic Tuna Management Plan. Information on the stock status or indicator is needed, since it is one essential component of a harvest strategy. In fact, the lack of catch and effort data from Indonesian fishery, in general, is still an international concern. A method to assess the stock status for data poor fisheries namely Length-based Spawning Potential Ratio (LB-SPR) was developed. This study attempted to investigate a possible use of the LB-SPR to estimate spawning potential ratios of SKJ using length data from Indonesian pole and line fishery collected by the port-based sampling program (a collaborative project between Indonesia and the Western and Central Pacific Fisheries Commission (WCPFC). There is a decreasing trend in the estimated SPR from 2010 to 2015 unless 2014, indicating that impact of fishing on the resources increased over the study period. If the SPR20% is adopted as limit SPR, then the estimated values of SPR less than SPR20% suggested that recruitment overfishing might be occurring. In fact, the results should be considered as preliminary results, as the size data of SKJ from pole and line might not be capturing large SKJ or the nature of SKJ in Archipealgic waters has smaller size in general compare to other region that potentially hampered the asymptotic selectivity assumption within the LB-SPR model underestimating the SPR. Further work is required to gather complete representative of length data of SKJ covering all length classes of the fishery.